A comparison of the ground reaction forces of archers with different levels of expertise during the arrow shooting - Simsek, D.; Cerrah, A. O.; Ertan, H.; Soylu, A. R. (Science & Sports, 2019)
Objective: The purpose of this study was to compare the differences in ground reaction forces (GRFs) of archers with different levels of expertise during arrow shooting. Material and methods: Twenty-seven male archers were involved in this study. Anterior-posterior ground reaction force (APGRF-Fy) and medio-lateral ground reaction force (MLGRF-Fx) collected by force platform during the successful shots towards the target from a distance of 18m. The center of pressure (CoP) excursion was computed during arrow shooting using the GRFs. All statistical analyses were completed using SPSS 22.0 for Windows software (SPSS Inc., Chicago, IL). The level of statistical significance was set as P<0.05. Results: Results demonstrated that elite group had the least CoP sway, APGRF and MLGRF during all phases comparing to both mid-level, beginner level archers. However the differences in APGRF and MLGRF between groups didn`t reach the significance level (P>0.05). The sway range of CoP values of elite group were significantly smaller than the values of beginner group (P<0.05). Conclusion: In conclusion, it was observed that the relationship between body sway and expertise level. Therefore instantaneous visual force feedback training including APGRF, MLGRF and CoP sway values could be recommended in order to increase shooting performance.